Factors Influencing Acute Exacerbation of Bronchial Asthma Among Children in Malaysia - Yadav, Rakhee; Yadav, Hematram; Leong, Tan Kok (International Journal of Child Health and Nutrition, 2014)
The aim of this study was to determine the factors influencing acute exacerbation of bronchial asthma among children in Malaysia. A cross-sectional study was done to identify the factors influencing acute exacerbation of asthma in the University Malaya Medical Centre. In this study 103 known asthmatic children between the ages of 2 to 12 years were analysed. Among the children, 60% had a family history of asthma, 39% allergic rhinitis and only 17% eczema. The main complaints were coryza (84%) and shortness of breath (88%). Majority of the patients were treated as out-patient (58%) and only two were admitted in Intensive Care Unit. The factors that were significantly associated with mild exacerbation compared to a moderate to severe exacerbation was well-controlled asthmatic, good compliance to medications and those who had regular follow up.